Strategi Pimpinan Lazisnu Dalam Peningkatan Kinerja Pegawai - H. Amin Awal Amarudin; Muhammad Rizvi (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
Leadership strategy has a significant role in the performance of organizations and social institutions. Leadership that is based on a good strategy and is supported by quality human resources has the potential to facilitate the achievement of goals and obtain more optimal performance results in an organization in accordance with the specified vision and mission. This research is motivated by the existence of an ideal institutional leadership, thereby creating employee performance discipline. This study aims to explain) to find out the strategy of the Lazisnu leadership in improving the performance of Lazisnu employees. The research method uses a qualitative approach, with descriptive analysis. The author attempts to conduct this research by using direct interviews with the leaders who are the primary data source for this research.